(untitled) (Western European Journal of Linguistics and Education, 2025)
This article explores the complexities of translating international words from English into Uzbek and Russian. It examines key challenges such as phonetic adaptation, grammatical differences, cultural relevance, semantic shifts, and the impact of globalization. By analyzing specific examples, the article highlights how these two languages handle English borrowings and adaptations differently, shedding light on the linguistic and cultural factors that influence translation